Photothermally active nanoparticles as a promising tool for eliminating bacteria and biofilms - Borzenkov, Mykola; Pallavicini, Piersandro; Taglietti, Angelo; D’Alfonso, Laura; Collini, Maddalena; Chirico, Giuseppe (Beilstein Journal of Nanotechnology, 2020)
Bacterial contamination is a severe issue that affects medical devices, hospital tools and surfaces. When microorganisms adhere to a surface (e.g., medical devices or implants) they can develop into a biofilm, thereby becoming more resistant to conventional biocides and disinfectants. Nanoparticles can be used as an antibacterial agent in medical instruments or as a protective coating in implantable devices. In particular, attention is being drawn to photothermally active nanoparticles that are capable of converting absorbed light into heat. These nanoparticles can efficiently eradicate bacteria and biofilms upon light activation (predominantly near the infrared to near-infrared spectral region) due a rapid and pronounced local temperature increase. By using this approach new, protective, antibacterial surfaces and materials can be developed that can be remotely activated on demand. In this review, we summarize the state-of-the art regarding the application of various photothermally active nanoparticles and their corresponding nanocomposites for the light-triggered eradication of bacteria and biofilms.
Keywords: antibacterial activity; bacteria eradication; nanoparticles; NIR light; photothermal effect